Needle penetration versus local anesthetic injection: which causes more pain during cranial nerve blocks for chronic migraine? - Marcelo Moraes Valença; Rita Santana dos Reis; Juliana Ramos de Andrade (Headache Medicine, 2026)
BackgroundPeripheral nerve blocks and sphenopalatine ganglion blocks are widely used in the treatment of chronicmigraine. Although generally considered minimally invasive, procedural discomfort may affect patientacceptance and adherence. The relative contribution of needle penetration and local anesthetic injectionto pain perception remains poorly characterized.ObjectiveTo compare pain associated with needle penetration and local anesthetic injection during a standardized360-degree headache block protocol in patients with chronic migraine.MethodsEight women (mean age 46 ± 17 years) diagnosed with chronic migraine according to ICHD-3 criteriaunderwent bilateral greater occipital, lesser occipital, auriculotemporal, and supraorbital nerve blocksusing 1 mL of 2% lidocaine per site administered through a 30-gauge insulin needle. Bilateral transnasalsphenopalatine ganglion blocks were also performed. Pain intensity was rated on a 0–10 numerical scaleimmediately after needle penetration and again after anesthetic injection. At the end of the procedure,patients rated overall procedural discomfort.ResultsAcross 8 patients, 64 nerve block sites were evaluated. Pain was significantly higher during 2% lidocaineinjection than during needle penetration (5.5 ± 3.2 vs. 3.7 ± 3.0; p < 0.001). Severe pain (scores 8–10)was reported at 20 of 64 sites 31.3% (20/64) during injection, compared with 9 of 64 sites 14.1% (9/64)during needle penetration. The supraorbital nerve block showed the highest mean pain scores duringboth needle penetration (4.8 ± 3.2) and anesthetic injection (6.0 ± 2.9). Nasal discomfort during thesphenopalatine ganglion block was mild (1.3 ± 1.8). Overall procedural discomfort was 6.4 ± 2.1.ConclusionsIn patients with chronic migraine undergoing a 360-degree headache block protocol, pain related to localanesthetic injection exceeded that associated with needle penetration. The supraorbital region appearedparticularly sensitive. Strategies aimed at reducing injection-related pain may improve patient toleranceand acceptance of repeated interventional headache procedures.